Comparison of Global and Regional Tidal Models at Sekupang Tidal Station - Siti Noor Chayati; Sefi Nuraeni (International ABEC, 2021)
Indonesia is an archipelagic country with a total marine area of 5.9 million km², consisting of 3.2 million km² of territorial waters and 2.7 km² of Exclusive Economic Zone waters, not including the continental shelf. With the vast waters in Indonesia, sufficient information about the tides is needed. However, in reality the number of tidal stations targeted by the Geospatial Information Agency (BIG), which is as many as 400 stations, has not been fulfilled. The data used in this study include tidal data at Sekupang station, global model data TPXO9 and regional model data from BIG. The components studied are the main components M2, K2, O1, and S1 using the Least Squares Adjustment method. The minimum discrepancy value is shown by the TPXO9 model, which means that the TPXO9 global model is a more suitable model to be used as a tidal prediction model in the waters of Batam Island.